MISTISISME JAWA PERSPEKTIF FENOMENOLOGI AGAMA Suatu Perbandingan antara Mistisisme Jawa, Hindu Dan Islam - Yohanes Murjiyono (Studia Philosophica et Theologica, 2004)
Javanese mysticism began before the coming of Moslem and Hinduism. The Javanese people believe in the spirit of ancestors. In its history, Javanese mysticism could not help but being influenced by Hinduism and Islam. The fact that it has been influenced by religions shows that Javanese mysticism appears richer. It is expressed in the idea of universe, human being and their relationship with The Holy. This study tries to grasp the thesis that pure Javanese mysticism is not there. Rather, Javanese Mysticism in this time is a more fusion of Javanese culture, Hinduism and Islamic Mysticism. This would be, in this article, the basis of inclusive point of view in modern Javanese society.